Leveraging symbolic systems to foster expressive communication in students with hearing impairments - Oronge Evernate Adhiambo; Onditi Sharon; Otara Alfred (Social Sciences and Humanities Open)
The study aimed to establish the contribution of symbols on the expressive language skills of learners with hearing impairments. The research used a mixed-method approach within a descriptive survey design, targeting a group of 73 learners, 46 teachers, 7 head teachers, and 5 Educational Assessment and Resource Centre officials (EARCs) who were purposefully chosen. Quantitative data from primary respondents were gathered using questionnaires and observation checklists, descriptively analyzed using means, frequencies, and standard deviation, and inferentially assessed by Pearson correlation, given in a table form. Qualitative data from the key informants was collected through interview guides and presented in narratives after thematic analysis. The findings reveal that the use of contextualized symbols through photographs, drawings, and picture cards enhance the expressive language skills of learners with hearing impairments. Their use should be complemented with other methods of teaching for a more comprehensive language skills acquisition. While some aspects of the findings may be consistent with the generally revealed trends of other studies, this study provides a more specific educational perspective in the Kenyan context. The research closes with suggestions for incorporating symbol-based communication tools into the curriculum for special education environments, with the objective of improving language development and communication abilities for learners with hearing impairments.